The Models of Narrators Whose Degrees Get Down by Al-Hafiz Ibn Hajar in his book“Taqreeb” from his other books - Harun, Mohammad Asem (Journal of Islamic Sciences, 2021)
The science of verifying narrators credible is one of the most important result of the efforts of Al-Hafiz Ibn Hajar Al-Asqalani- may God have mercy on him- He used to follow the men and judge them, and his judgment became an important reference for those who came after him from among the researchers, and indeed many of them relied on his judgment in their judgment on the narrators. However, his sayings differed in judging some of the narrators, so we find that he judges some in one book with a ruling, and he is judged by another in another book of his. Who urges me to carefully consider his method of verifying the narrators; In order to trace that difference, with an attempt to identify its causes, and to clarify the correctness of it? Through the study of five narrators, prefacing the way by an explanation of the ranks of verifying narrators according to Al-Hafiz Ibn Hajar, the reasons for the difference in his sayings, and the Theory for choosing the most correct saying according to him. Concluding with the most important results that I have reached from this study. At las I ask Allah to be of benefit and benefit to the writer and the reader, he is the Guardian of that and the capable of it, and praise be to God, Lord of the Worlds, and prayers and peace be upon our Prophet Muhammad and all his family and companions.